2022
DOI: 10.1155/2022/1316409
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Food Insecurity and the Choice of Livelihood Strategies: The Case of Abay Chomen District, Oromia Regional State, Ethiopia

Abstract: Most of the sub-Saharan African countries including Ethiopia were affected by the food insecurity issue. This study aimed to analyze the drivers of food insecurity, the choice of livelihood strategies, and factors that impact the choices of food security strategies in response to food insecurity in Abay Chomen District of Ethiopia’s Oromia region, Ethiopia. The result of this study is based on primary data and obtained from 150 randomly chosen sample households and secondary data generated from various sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Hence, households with larger dependency ratio should diversify their livelihood strategy so as to earn additional income for fulfilling their family felt needs. This result coincides with the findings of [22] who reported that families with larger dependency ratio have idler and non-productive family members with larger demand for food and other obligatory family needs. However, this result contradicts with the finding of [9] which reported "household with larger dependency ratio faced shortage of working hands to earn from diversified activities for meeting their family needs".…”
Section: Determinants Of Household Choice Of Livelihood Diversificati...supporting
confidence: 91%
“…Hence, households with larger dependency ratio should diversify their livelihood strategy so as to earn additional income for fulfilling their family felt needs. This result coincides with the findings of [22] who reported that families with larger dependency ratio have idler and non-productive family members with larger demand for food and other obligatory family needs. However, this result contradicts with the finding of [9] which reported "household with larger dependency ratio faced shortage of working hands to earn from diversified activities for meeting their family needs".…”
Section: Determinants Of Household Choice Of Livelihood Diversificati...supporting
confidence: 91%
“…Agricultural machinery (X3) and Relationship with friends and relatives (X5) have also been referenced by Liu and Liu [19]. The variable Income household (X4) has been discussed by Gebissa and Geremew [20]. Farmer perception (X1.3) has been addressed by Okonya et al [21].…”
Section: Data Analysis and Variable Selectionmentioning
confidence: 99%
“…When farmers have good financial conditions, they are more likely to invest capital in new farming activities. Household income positively impacts their livelihood choices, making it easier for them to invest and overcome financial constraints to make a new model [20].…”
Section: The Analysis Of Factors Affecting the Change In Agricultural...mentioning
confidence: 99%
“…Previous research relating to nutrition and traditional food markets has tended to focus more on an agricultural perspective. For example, how agriculture and livestock practices are associated with market access and income and in turn how this is linked to food and nutrition insecurity (Gebissa and Geremew, 2022;Sibhatu et al, 2022). Affordability and access to foods in markets and income have been found to be associated with food security (Keding et al, 2017;McCordic et al, 2019;Middendorf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the relevance of the gender of the head of a household in nutrition and food security in respect of decision making around access to resources and labor (Ochieng et al, 2017). Differences are also seen between males and females, regarding income generation, market access, and finances due to different roles in markets and duties outside of food production and acquisition (Gebissa and Geremew, 2022;Milner et al, 2022;Sibhatu et al, 2022). Markets can provide space for women to be involved in food purchasing and income generation, but this research is still limited (Davies et al, 2022).…”
Section: Introductionmentioning
confidence: 99%